A PRELIMINARY STUDY OF THE COLEMANITE-RICH TUFF LAYER FROM THE SOURIDES AREA, KARLOVASSI BASIN, SAMOS ISLAND, HELLAS - Kantiranis, N.; Filippidis, A.; Stamatakis, M.; Tzamos, E.; Drakoulis, A. (Bulletin of the Geological Society of Greece, 2007)
Representative 3 kg sample of a colemanite-bearing tuffaceous layer from Sourides village of Samos Island have been investigated for its mineralogical and chemical composition using Light Microscopy, X-Ray Powder Diffraction and Atomic Adsorption Spectroscopy methods. The studied sample contains 68 wt. % colemanite, consisting of 31.1 wt. % B203 and 28.4 wt. % CaO. The mineralogical and chemical composition of the sample, after calcination could produce a concentrate containing 43-44 wt. % B203, fulfill at least one of the commercial specifications for the calcined colemanite concentrates.